Translation and minority, lesser-used and lesser-translated languages and cultures - Debbie Folaron (JoSTrans: The Journal of Specialised Translation)
Over the past decade, there have been repeated calls by linguists and institutions to recognise and protect languages that are not considered to be 'majority' or 'world' languages. Indigenous, aboriginal, minority, minor, lesser-used: they constitute about 90% of the world's 7000 languages. A growing number of articles and essays have also been devoted to discussing lesser-translated languages. It is interesting to note that although many nation-states throughout the world have some type of bilingual or multilingual language policy in place, these language policies do not always confer equal status to translation policies. Furthermore, they often bypass 'living languages' spoken within national territories. Indeed, in many areas of the world, multilingualism is the norm rather than the exception. Preserving and revitalising those living languages slowly facing extinction has gained high priority status in some sectors, and several projects have materialised to address the shifts that lead to language loss. The struggle to sustain languages in danger often equally implies the need to redress longstanding problems of marginalisation, stigmatisation and misrepresentation. Meanwhile, the globalising digital world and technologies are recontextualising many individual and collective social practices in relation to minority, minor, lesser-used, and endangered language communities. It is clear that translation activities ─ including audio-visual and multimedia translation, localisation, terminology creation and management, interpreting, etc. ─ play a significant role in these changing practices. The current issue explores some of these diverse aspects.